Performance appraisal process: exploring the effects of distributive justice perceptions and perceived accountability - McCalla, Nena E. (University of Wisconsin--Stout, 2018)
Employees' organizational justice perceptions are an integral part of research regarding performance appraisal process. Organizational justice is broadly described as the perceived level of fairness employees have in an organization (Greenberg, 1987). The current paper is an empirical test of a portion of the performance appraisal process model proposed by Erdogan (2002), which suggests that the perceived fairness of one's performance ratings leads to accountability perceptions, which, in turn impacts performance-related outcomes (i.e., motivation to improve and task performance). The researcher hypothesized positive relationships between favorable ratings, distributive justice perceptions, perceived accountability, and performance-related outcomes. In addition, distributive justice and perceived accountability were predicted to mediate the relationship between performance ratings and subsequent performance behaviors and motivation. To examine the hypotheses, a true experimental design (N = 91) was implemented utilizing a Midwestern University sample of undergraduate students. Participants were asked to participate in proof reading and editing tasks, as well as asked about rating their level of perceptions on a variety of questions. Results showed that favorability ratings were positively associated with justice perceptions and justice perceptions were positively related to perceived accountability, but the serial mediation was not supported.
Keywords: Distributive justice; Universities and colleges; Performance standards